2011
DOI: 10.2519/jospt.2011.3354
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Adaptation and Validation of the VISA-P Questionnaire for German-Speaking Patients With Patellar Tendinopathy

Abstract: valid questionnaire for the self-assessment of pain, symptoms, and function in German-speaking patients with patellar tendinopathy. Its psychometric properties are comparable with the original English and international adaptations (Swedish, Dutch, and Italian).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
65
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 22 publications
14
65
0
5
Order By: Relevance
“…This adaptation showed good psychometric properties in Spanish athletes, and that the scores of the groups were very similar to those obtained from subjects using other versions 12,28,29,37,39 of the same scale supports our findings.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This adaptation showed good psychometric properties in Spanish athletes, and that the scores of the groups were very similar to those obtained from subjects using other versions 12,28,29,37,39 of the same scale supports our findings.…”
Section: Discussionsupporting
confidence: 79%
“…As the authors suggested in the original publication, the VISA-P should not be considered a diagnostic tool, because there were no significant differences between the scores of athletes with tendinopathy and those of patients with other knee injuries. 12,28,29,39 In the study of VISA-P-Sp correlation with SF-36 components, participants with higher levels of symptoms had, as expected, a poorer quality of life related to health. This finding helps to confirm the external validity of the questionnaire and its adaptation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4,6,26,32 Before a questionnaire can be used to assess individuals from other countries who speak a different language, it must be translated into that language and culturally adapted to the country in which it is to be used. 14,18 For example, questions related to activities of daily living or sports that are uncommon in the target country may require adaptations beyond simple translation. In addition, before it can be used in either a clinical or research context, the psychometric properties of the translated version of the questionnaire must be established.…”
Section: T T Conclusionmentioning
confidence: 99%